Eficiência e rivalidade: alternativas para o direito da concorrência nos países em desenvolvimento - Bruno Braz de Castro (2017)
The understanding of the goals of competition law, in Brazilian legal-economic order, must be aligned to the constitutional ideology, which guides the infra-constitutional economic policy to the promotion of economic development, under the benchmark of social justice. This thesis intends to answer the following question: is economic efficiency, as defined by the Chicago School ideology, to be understood as the single and ultimate goal of competition law in Brazil, considering its developing country status? The hypothesis is that, answering to the constitutionally adopted ideology, the goal of Brazilian competition law must incorporate the protection of rivalry, to the extent that it fosters the ultimate constitutional goal of inclusive economic development. To answer the research question the thesis demonstrates that although accompanied by a political neutrality discourse, the Chicago antitrust theory is embedded in an ideology. According to its worldview on the role of the state and the firm in the economic order, it defines which economic values must be included or excluded from the analysis of the desirability of economic practices. In particular, Chicago ideology excludes distributional and dynamic concerns, among other values. The guidelines to the implementation of an economic efficiency-based framework are also based on a decision theory which stipulates costs of errors, built on questionable assumptions. These arguments call into question the universal character of Chicago antitrust theory. Further, the thesis demonstrates that the Brazilian Constitution is itself embedded in ideology, according to which the economic order must be devoted to fostering economic development under a social justice framework. Hence, the theoretical proposals related to a differentiated understanding of the role of competition law in developing countries aiming at the protection of the competitive process and the preservation of rivalry in order to foster inclusive economic development are deemed fitting to the Brazilian setting. This understanding favors a renewed focus on abuses of dominant position in the Brazilian antitrust enforcement policy. Finally, through a comparative study of the USA and EU case law concerning margin squeezes, the thesis demonstrates that rivalry concerns drive the equally efficient competitor test in EU jurisprudence. The European experience should, therefore, constitute the starting point to the analysis of such economic conduct in the Brazilian system. It is acceptable, however, that the Brazilian analysis doesn't restrict itself to such starting point, in order to attend to characteristics of its economic reality. The research is justified in the light of the recent discussions on the international convergence of competition law. The debate identifies possible adverse consequences of legal transplants when this process takes place without proper regard to the legal system and economic reality of the recipient country.